Virtual reality simulation: Bobsled and luge - Levy, R. M.; Katz, L. (2007)
This research paper examines the effectiveness and potential benefits of different simulation environments in the sliding sports of bobsled and luge. Visualization techniques have been critical components in training athletes for the psychological stress associated with a competition. Studies reveal that an athlete`s performance can benefit from programs that use some aspect of visualization. Our focus is on the visualization experiences of driving a bobsled and steering a luge sled within a virtual world. The lessons learned from this research are being used to design future versions of simulators for training Olympic athletes engaged in sliding sports.